Study on the effect of water content on physical properties of bentonite. - Chao Zheng; Yanzhao Yuan (PLoS ONE)
Moisture content profoundly influences the engineering properties of expansive soil, a critical consideration in various geotechnical applications. This study delves into the intricate relationship between water content and the physical properties of bentonite, a key constituent of expansive soil. Through a comprehensive analysis encompassing fundamental physical properties, rheological characteristics, permeability behavior, and microscopic features, we elucidate the complex interplay between water content and bentonite behavior. Our investigation reveals distinct responses to varying moisture levels: at low water content (w = 50%), unsaturated samples undergo incremental density increases attributed to moisture accumulation among particles. Concomitantly, heightened pressure fosters enhanced cohesion between particles, bolstering mechanical properties and augmenting reverse osmosis capacity. Conversely, at higher water content levels (w > w saturated), the escalation of free water within soil particles triggers pronounced particle softening, overshadowing expansion effects. Consequently, cohesion diminishes, and particles exhibit micro-scale flocculation. These findings offer valuable insights into bentonite behavior under differing moisture regimes, thereby providing a robust theoretical foundation for projects requiring bentonite seepage control.